2023
DOI: 10.1186/s12998-023-00486-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations and levels of satisfaction in chiropractic treatment for lumbar radiculopathy. A mixed methods study

Rikke Krüger Jensen,
Sille Lillesø,
Jack Starche Jensen
et al.

Abstract: Background Chiropractic patients are generally satisfied with the care received. It is unclear if this also applies to Danish patients with lumbar radiculopathy included in a standardised chiropractic care package (SCCP). This study aimed to investigate patient satisfaction and explore perspectives on the SCCP for lumbar radiculopathy. Methods An explanatory sequential mixed methods design with three separate phases was used. Phase one was a quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
3
0
0
Order By: Relevance
“…Respondents reported reduction in pain and improvements in function after treatment. This is consistent with other studies [ 20 , 38 , 43 ]. Herman [ 21 ], found high rates of satisfaction in chiropractic patients with chronic low back and neck pain with reasons including avoiding narcotics and surgery, which did not feature in our study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Respondents reported reduction in pain and improvements in function after treatment. This is consistent with other studies [ 20 , 38 , 43 ]. Herman [ 21 ], found high rates of satisfaction in chiropractic patients with chronic low back and neck pain with reasons including avoiding narcotics and surgery, which did not feature in our study.…”
Section: Discussionsupporting
confidence: 94%
“…We found that the respondents in this study generally reported a positive perception of their experiences. This is consistent with other chiropractic studies on a variety of populations [ 18 21 , 23 , 24 , 38 41 ]. In addition, Hurwitz in 2012 [ 42 ] reviewed the literature and found high satisfaction among patients of clinicians who employed spinal manipulation, including chiropractors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation